PERLINDUNGAN HUKUM TERHADAP NASABAH PENYIMPAN DANA PADA BANK YANG DILIKUIDASI MENURUT UNDANG-UNDANG NOMOR 24 TAHUN 2004 TENTANG LEMBAGA PENJAMIN SIMPANAN - Zuriyati '; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The liquidation of a bank will have an impact on customer confidence, especially if the bank is unable to pay its obligations to its customers, it will eliminate the customer confidence in the banking institutions. Deposit Insurance Agency (LPS) is an independent organization that works to implement the deposit guarantee and participate actively maintaining banking stability. This study aims to discuss issues about the shape of the legal protection of depositors in the bank liquidated if savings exceed the amount guaranteed by LPS and what the legal consequences according to Law No. 24 of 2004 concerning the Deposit Insurance Agency.This study uses normative law research. Data collection techniques used literature study method or documentary studies. Source of data used are secondary data consists of primary legal materials, secondary law and tertiary legal materials. Data were analyzed using qualitative data analysis with descriptive parse.From the results of this study concluded that the form of legal protection for depositors due to the liquidation of the bank before the establishment of the Law No. 24 of 2004 concerning the Deposit Insurance Agency (LPS) is very weak because only through implicit protection. After the birth of the LPS Act provide protection and legal certainty for depositors both directly and indirectly. The legal consequences of the liquidation of a bank to depositors with funds in excess of LPS will receive payment from the sale of bank assets in the liquidation process, in accordance with the provisions of Article 54 Paragraph 1 of the Law of LPS, as well as for the deposit is not guaranteed as eligible contained in Article 19 may submit an objection to LPS or file a lawsuit to court. If the sale of bank assets are insufficient to repay depositors deposits, depositors may file a lawsuit to existing shareholders or parties proved to cause the bank to a bank failure by the District Court.Keywords : Customer Protection - Deposit Insurance Agency – Liquidation Bank